All things bright and beautiful: Liturgy for sustainable living - Scott, Hilton (Stellenbosch theological journal, 2021)
In this article an investigation is begun endeavouring to understand what role the worship service has to play in promoting sustainable living. Comparisons are drawn from culture and tradition, which sees hymns such as "All things bright and beautiful" to be examples of the people celebrating God's gracious gift of creation. It is suggested, through describing three perspectives, that liturgy can be a space for encouraging sustainable living. This is possible by (1) identifying that liturgy can be a space against waste, (2) that certain aspects of culture and tradition can combine in a critical-reciprocal manner to create a new entity and (3) by understanding that worship affects belief and thought, which in turn affects how "we" live and/or vice versa.